Gambaran Pemanfaatan Antenatal Care Selama Pandemi Covid-19 - Meo, Maria Lupita Nena; M, Adriani Natalia; Lumentut, Anastasia Marine (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2025)
Background: Movement restriction policies and social restrictions are implemented by several countries as an effort to suppress the spread of the covid-19 virus. However, these restrictions on movement (lockdown) and social restrictions have an impact on limiting the use of health facilities by all communities, including the use of antenatal care (ANC) services.Objectives: This study aims to provide an overview of the use of ANC services by pregnant women during the COVID-19 pandemic situation.Methods: This study is a quantitative study with a cross-sectional survey design conducted in 3 health centers in Manado City. The number of respondents who participated in this study were 90 pregnant women who were recruited using simple random sampling technique. Data were collected using questionnaires and analyzed using descriptive analysis.Results: The results showed that most pregnant women 58.% did not regularly perform ANC during the covid 19 pandemic. The proportion of pregnant women who received iron during ANC was 62%, the proportion of pregnant women who received folic acid was 53% and the proportion of pregnant women who received iron. received TT immunization was 29%.Conclusion: During the covid 19 pandemic, most pregnant women did not regularly use ANC services. This is due to restrictions on ANC services. It is necessary to empower pregnant women to carry out simple checks at home, and to optimize health consultations for pregnant women via telephone and social media.